2020
DOI: 10.3390/sym12061014
|View full text |Cite
|
Sign up to set email alerts
|

A Double Generally Weighted Moving Average Chart for Monitoring the COM-Poisson Processes

Abstract: Generalized exponentially weighted moving average (EWMA) and double EWMA (DEWMA) charts based on the Conway–Maxwell–Poisson (CMP or COM-Poisson) distribution, also known as the GEWMA and CMP-DEWMA charts, are effectively used for monitoring the counts of non-conformities in a process. To further enhance their performance, this study utilizes design and adjustment parameters to develop generally weighted moving average (GWMA) and double GWMA charts, also known as the CMP-GWMA and CMP-DGWMA charts, to monitor CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Since data dispersion cannot be identified beforehand, an expanded Poisson distribution called the Conway and Maxwell Poisson (denoted as COM‐Poisson) takes into account both location and dispersion parameters. Hence, Chen 60 proposed the GWMA COM‐Poisson scheme, which is shown to yield a better small shifts performance than the EWMA COM‐Poisson scheme. The latter conclusion holds in many situations when monitoring location parameter only or simultaneously monitoring location and dispersion parameters, but over the entire range of shifts when monitoring dispersion only (except in very few instances with a large dispersion parameter).…”
Section: Gwma Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since data dispersion cannot be identified beforehand, an expanded Poisson distribution called the Conway and Maxwell Poisson (denoted as COM‐Poisson) takes into account both location and dispersion parameters. Hence, Chen 60 proposed the GWMA COM‐Poisson scheme, which is shown to yield a better small shifts performance than the EWMA COM‐Poisson scheme. The latter conclusion holds in many situations when monitoring location parameter only or simultaneously monitoring location and dispersion parameters, but over the entire range of shifts when monitoring dispersion only (except in very few instances with a large dispersion parameter).…”
Section: Gwma Schemesmentioning
confidence: 99%
“…Next, Huang et al 75 proposed a DGWMA SoS scheme and showed that it has a better ARL and SDRL detection ability than the corresponding DEWMA and GWMA SoS schemes in many situations. More recently, Chen 60 showed that the DGWMA COM‐Poisson scheme has better small shifts detection ability (in monitoring location, dispersion, and the latter two simultaneously) than the EWMA, DEWMA, and GWMA COM‐Poisson schemes.…”
Section: Dgwma Schemesmentioning
confidence: 99%
“…11 The PEWMA chart using a ranked set sampling scheme has been suggested by Abujiya et al 12 The extended work on PGWMA has been developed by Chiu and Lu, 13 Chiu and Sheu, 14 and Chen. 15 Abbasi 16 developed Poisson progressive mean (PPM) charts under the zero and steady-state situations. The interested readers are referred to Rakitzis et al, 17 Morais et al, 18 Cabral Morais and Knoth, 19 Abbas et al, 20 and Aly et al 21 for more literature on Poisson charting schemes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mentioned procedures require excellent expertise, high computational efforts, and time. The Conway-Maxwell (COM)-Poisson (COM-Poisson) model proposed by Guikema and Goffelt [45] is the better alternative, which is a flexible model and able to handle any type of disperse data [46]. Lord et al [47] and Lord et al [48] have successfully used COM-Poisson regression to model the traffic crash data.…”
Section: Introductionmentioning
confidence: 99%